In situ redox speciation analysis of chromium in water by diffusive gradients in thin films using a DE81 anion exchange membrane - Suárez, Carlos A. [UNESP]; De Simone, Thays V. [UNESP]; Menegário, Amauri A. [UNESP]; Rolisola, Ana M.C.M. [UNESP]; Luko, Karen S. [UNESP]; Gastmans, Didier [UNESP]; Da Conceição, Fabiano T. [UNESP]; Kiang, Chang H. [UNESP] (Elsevier, 2016)
A method for the in situ redox speciation analysis of chromium in water by the diffusive gradients in thin films (DGT) technique using a DE81 anion exchange membrane was successfully developed. For the selective uptake of Cr(VI), a DGT device containing an anion exchange membrane DE81 (cellulose acetate chromatographic paper) was used (DE81-DGT), while selective uptake of Cr(III) was carried out using DGT devices containing the Chelex-100 resin (Chelex-100-DGT). A correlation coefficient of 0.993 was obtained for the linearity of the immersion curves (mass versus time) using DE81-DGT. The diffusion coefficient values for Cr(VI) through the agarose diffusive layer were equal to 4.89±0.5×10-6 cm2 s-1 and 3.95±0.02×10-6 cm2 s-1 (T=23±1°C, I=0.03 mol L-1 NaNO3) were obtained by using diffusion cell and immersion curves, respectively. The retention of Cr(VI) by the DE81 membrane in a synthetic sample and river water was not affected by the pH over a wide range 4-9). Recoveries of Cr(VI) between 90% and 120% from solutions of ionic strength ranging from 0.01 to 0. 5 mol L-1 NaNO3 were achieved. Finally, the redox speciation analysis of Cr(III) and Cr(VI) in spiked river water and synthetic samples was performed with recoveries greater than 80% and 87% by using Chelex-100-DGT and DE81-DGT devices, respectively. Those results were in excellent agreement with the diphenylcarbazide spectrophotometric method.
Keywords: Chromium speciation; DE81 membrane; Diffusive gradients; Paper-based DGT; Passive sampler; Thin films